Injury Prevention Strategy Training in Esports Players: A Holistic Approach to Physical and Mental Health - Saefullah, Rifki; Yohandoko, Setyo Luthfi Okta; Lianingsih, Nestia (International Journal of Ethno-Sciences and Education Research, 2024)
Esports has grown into a global industry that attracts the attention of millions of players around the world. However, the popularity and intensity of the game has brought a risk of injury to esports players, especially related to physical problems such as hand joint injuries and poor posture. This article describes various injuries that often occur in esports players, including injuries to hand joints, posture disorders, eye disorders, sleep disorders, and mental health. We also explain the factors that can cause this injury, such as repetitive movements, high pressure, unergonomic positions, lack of rest, joint stiffness and psychological stress. Next, we present comprehensive solutions to prevent injuries in esports players, including physical exercise, stretching exercises, use of ergonomic equipment, attention to body posture, playing time management, and mental health care. Emphasis is placed on a holistic approach that includes both physical and mental health.